Hydration measurement by bioimpedance spectroscopy and blood pressure management in children on hemodialysis - Zaloszyc, Ariane; Schäfer, Betti; Schaefer, Franz; Schmitt, Claus P. (Pediatric nephrology, 2013)
Background: Hypertension is frequent in chronic hemodialyzed patients and usually treated by reducing extracellular fluid. Probing dry weight only based on a clinical evaluation may be hazardous, especially in case of volume independent hypertension. Methods: We performed a 1-year retrospective study in three pediatric centers to define the relation between blood pressure (BP) and hydration status, assessed by whole-body bioimpedance spectroscopy (BIS). We analyzed 463 concomitant measurements of BP, relative overhydration (rel.OH), and plasma sodium (Napl) in 23 children (mean age 13.9 ± 5.1 years). Results: Pre-dialytic under-hydration (rel.OH < −7 %) was present in 5.4 % of the sessions, out of which 24 % showed hypertension. Normohydration (rel.OH −7 – +7 %) was observed in 62.4 % of the sessions, 45.3 % of them revealed hypertension. Moderate OH (rel.OH +7 – +15 %) was present in 21 % of the sessions, 47.4 % of them showed normal BP. In 11.2 % of the sessions, severe overhydration (rel.OH > +15 %) was assessed, however, the majority (73 %) showed normal BP. Patient-specific Napl setpoint could not be described. Mean dialysate sodium concentration was higher than mean Napl. Conclusions: Hypertension is not always related to overhydration. Therefore, BIS should restrict the practice of “probing dry weight” in hypertensive children. Moreover, sodium dialytic balance needs to be considered to improve BP management.
Gesehen am 26.07.2021